Extremely metal-poor galaxies with HST/COS: laboratories for models of low-metallicity massive stars and high-redshift galaxies. Issue 3 (11th July 2019) - Senchyna, Peter; Stark, Daniel P; Chevallard, Jacopo; Charlot, Stéphane; Jones, Tucker; Vidal-García, Alba
Abstract: Ultraviolet (UV) observations of local star-forming galaxies have begun to establish an empirical baseline for interpreting the rest-UV spectra of reionization-era galaxies. However, existing high-ionization emission line measurements at z > 6 (W_C IV, 0 20 Å) are uniformly stronger than observed locally (W_C IV, 0 2 Å), likely due to the relatively high metallicities (Z/Z > 0.1) typically probed by UV surveys of nearby galaxies. We present new HST /COS spectra of six nearby ( z < 0.01) extremely metal-poor galaxies (XMPs, Z/Z ≲ 0.1) targeted to address this limitation and provide constraints on the highly uncertain ionizing spectra powered by low-metallicity massive stars. Our data reveal a range of spectral features, including one of the most prominent nebular C iv doublets yet observed in local star-forming systems and strong He ii emission. Using all published UV observations of local XMPs to date, we find that nebular C iv emission is ubiquitous in very high specific star formation rate systems at low metallicity, but still find equivalent widths smaller than those measured in individual lensed systems at z > 6. Our moderate-resolution HST /COS data allow us to conduct an analysis of the stellar winds in a local nebular C iv emitter, which suggests that some of the tension with z > 6 data may be due to existing local samples not yet probing sufficiently high α/Fe abundance ratios. Our results indicate that C iv emission can play a crucial role in the JWST and ELT era by acting as an accessible signpost of very low metallicity (Z/Z < 0.1) massive stars in assembling reionization-era systems.